Epidemiology of Hospitalized Traumatic Pelvic Fractures and Their Combined Injuries in Taiwan: 2000–2011 National Health Insurance Data Surveillance. (1st April 2014) - Yang, Nan-Ping; Chan, Chien-Lung; Chu, Dachen; Lin, Yu-Zhen; Lin, Kai-Biao; Yu, Ching-Shao; Yu, I-Liang; Chang, Nien-Tzu; Lee, Yi-Hui
Abstract : Background . From the viewpoint of prehospital emergency medicine, a greater proportion of pelvic fractures not of a life-threatening status but combined with other injuries need more comprehensive recognition. Methods . A 12-year nationwide health database of inpatients was reviewed. All cases diagnosed as pelvic fractures were enrolled. The associated injuries classified into 20 categories were further analyzed. Results . During 2000–2011, the hospitalized incidence of pelvic fractures in Taiwan ranged from 17.17 to 19.42 per 100, 000, and an increasing trend with age was observed. The mean case-fatality rate was 1.6% for females and 2.1% for males; male patients with pelvic fractures had a significantly higher risk of death than female patients after adjusting for other covariates. 74.2% of these cases were combined with other injuries. The most common associated injuries in an identified body region were other orthopedic fractures of the lower limbs (21.50%), spine/trunk (20.97%), or upper limbs (18.18%), followed by significant head injuries (17.59%), intra-abdominal injuries (11.00%), and thoracic injuries (7.20%). Conclusion . The incidence of hospitalized pelvic fractures in Taiwan was low and the case-fatality rate was lower than those of other countries. Concurrently, coexistence of major combined injuries with pelvic fractures was easily treated at medical centers.